United States Foreign Policy in the Last Third of the 19th Century: a Historiographical Review - Sánchez Padilla, Andrés (Revista Complutense de Historia de América, 2016)
This article examines the latest debates in North-American historiography on the foreign policy of the United States in the last third of the 19th century, relating them to Spanish historiography. To begin with, the contributions of the principal historiographical schools, from Realism to Cultural Studies, are first reviewed. Subsequently, the case is made that Spanish historiography has not paid sufficient attention to what has been written about this in the United States. The article ends by providing some suggestions for the improvement of the state of the academic debate on either side of the Atlantic.